Acquired vaginal stenosis following caesarean delivery: a case report - Ray Das, Chandana; ., Alakananda; Bora, Rakhi; Das, Bonani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Postpartum genital tract adhesions are infrequent and their reason has not been appraised. Though, severe dystocia and frequent pelvic examinations have been projected as possible causes. Here, we report a case of vaginal adhesions following caesarean section for obstructed labour that presented as irregular menstruation with desire to remove the PPIUCD. The patient was successfully treated with surgical resection.